2021
DOI: 10.1021/acsami.1c08107
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional Dendrimer Micelles with Glycyrrhizic Acid for Anti-Inflammatory Therapy of Acute Lung Injury

Abstract: Dendrimer micelles with glycyrrhizic acid (GA) were developed for anti-inflammatory therapy of acute lung injury (ALI). Cholesterol was conjugated to histidine-and argininegrafted polyamidoamine (PamHR) for micelle formation. The cholesterol-conjugated PamHR (PamHRchol) was mixed with amphiphilic GA to produce PamHRchol/GA mixed micelles. The GA integrated into the micelles had two functions: it acted as an anti-inflammatory drug and facilitated intracellular gene delivery. The PamHRchol/GA micelles formed sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…The investigators extracted the abstracts and titles and identified 38 studies that met the inclusion criteria. After reviewing all of the publications, 10 studies were excluded because of missing outcome data ( Ehrhart et al, 2000 ; Tawadros et al, 2007 ; Nader and Baraka, 2012 ; An et al, 2014 ; Wang et al, 2015 ; Liu and Chen, 2016 ; Shen et al, 2017 ; Ni et al, 2019 ; Wang et al, 2019 ; Yang et al, 2019 ), and another 12 studies were excluded because multiple interventions were investigated ( Murakami et al, 2000 ; Lin et al, 2011 ; Li et al, 2014b ; Li et al, 2016a ; Li et al, 2016b ; Baradaran Rahimi et al, 2019 ; Ye et al, 2019 ; Duan et al, 2020 ; Yue et al, 2020 ; Choi et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022 ). In conclusion, 16 studies were included in this meta-analysis, as described below ( Shi et al, 2007 ; Yang et al, 2011 ; Chen et al, 2014 ; Yang et al, 2014 ; Yuan et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ; Ren et al, 2019 ; Zhang et al, 2020 ; Ali et al, 2021 ; Dikmen et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The investigators extracted the abstracts and titles and identified 38 studies that met the inclusion criteria. After reviewing all of the publications, 10 studies were excluded because of missing outcome data ( Ehrhart et al, 2000 ; Tawadros et al, 2007 ; Nader and Baraka, 2012 ; An et al, 2014 ; Wang et al, 2015 ; Liu and Chen, 2016 ; Shen et al, 2017 ; Ni et al, 2019 ; Wang et al, 2019 ; Yang et al, 2019 ), and another 12 studies were excluded because multiple interventions were investigated ( Murakami et al, 2000 ; Lin et al, 2011 ; Li et al, 2014b ; Li et al, 2016a ; Li et al, 2016b ; Baradaran Rahimi et al, 2019 ; Ye et al, 2019 ; Duan et al, 2020 ; Yue et al, 2020 ; Choi et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022 ). In conclusion, 16 studies were included in this meta-analysis, as described below ( Shi et al, 2007 ; Yang et al, 2011 ; Chen et al, 2014 ; Yang et al, 2014 ; Yuan et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ; Ren et al, 2019 ; Zhang et al, 2020 ; Ali et al, 2021 ; Dikmen et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…GA is the main active ingredient in licorice, which is a traditional Chinese medicine that is safe and non-toxic . It is a natural anti-inflammatory and antibacterial drug commonly applied in the treatment of acute lung injury, chronic pneumonia, and pulmonary fibrosis. ,, Although GA does appear to be used in many cases to treat respiratory diseases, it is unclear whether it cures CRD in chickens caused by MG. In this study, GA was adopted in the cellular model and the chick model to investigate its effect on MG infection and molecular mechanism, to provide a theoretical basis for GA in clinical treatment of CRD, and for further development of safe, effective, and cheap antibiotic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase assay showed that the in vitro plasmid DNA delivery efficiency of pDNA/PamChol Cur delivered to lung epithelial cells was significantly higher than that of the pDNA group and exerted anti-inflammatory effects by inhibiting the nuclear translocation of NF-κB (Kim et al, 2019). Choi et al (2021) used cholesterol coupled to histidine and arginine grafted polyamidoamine (PamHR) to form micelles (PamHRchol), followed by a reaction with glycyrrhizic acid (GA) to produce mixed dendritic micelles (PamHRchol/GA), and the HO-1 gene was introduced into the lungs of ALI mice as a therapeutic gene. Dendrimeric micelles have higher gene delivery efficiency compared to free GA.…”
Section: Nanocapsulementioning
confidence: 99%